Fixed Point Theorems for Semigroups of Lipschitzian Mappings - Saiful Marom; Muhammad Istiqlal (Pandawa Institute, 2024)
The main purpose of this paper is to extend the results of fixed point theorems for lipschitzian semigroups. The proofs we give follow the results of Ishihara, Suantai and Puengrattana theorems. Using one of the proofs, we also develop a fixed point theorem result for nonempty asymptotically total mapping semigroups on uniformly convex Banach spaces.